1967
DOI: 10.1085/jgp.50.6.1807
|View full text |Cite
|
Sign up to set email alerts
|

Is the Cell Membrane a Universal Rate-Limiting Barrier to the Movement of Water between the Living Cell and Its Surrounding Medium?

Abstract: With the use of a newly introduced technique, the "influx profile analysis," we studied the diffusion of tritiated water in and out of frog ovarian eggs at 25°C. The results show that the rate-limiting step in the exchange of labeled water is not permeation through the cell membrane but diffusion in the bulk of the intracellular water.Eighty-eight years ago Pfeffer postulated that the cell membrane is a universal barrier to the traffic of all solutes and water, i.e. all resistance to water movement lies in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1969
1969
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…From these studies they reached the conclusion that the majority of cell water has strongly reduced translational and rotational motional freedom. Their findings are in agreement with the predictions of the polarized multilayer th:!ory of cell water (Ling, 1965(Ling, , 1967Ling, Ochsenfeld, and Karreman, 1967). Just as exciting was the finding of Rorschach and coworkers that similar neutron-scattering studies revealed water associated with 36% PEO exhibits properties of translational and rotational motional restrictions similar to the water in the Artemia cysts (Rorschach, personal co~nunication).…”
Section: Freezing Propertiessupporting
confidence: 78%
“…From these studies they reached the conclusion that the majority of cell water has strongly reduced translational and rotational motional freedom. Their findings are in agreement with the predictions of the polarized multilayer th:!ory of cell water (Ling, 1965(Ling, , 1967Ling, Ochsenfeld, and Karreman, 1967). Just as exciting was the finding of Rorschach and coworkers that similar neutron-scattering studies revealed water associated with 36% PEO exhibits properties of translational and rotational motional restrictions similar to the water in the Artemia cysts (Rorschach, personal co~nunication).…”
Section: Freezing Propertiessupporting
confidence: 78%
“…Thus, a t least some of the yolk platelet water would appear to be multifold slower in its diffusion than the majority of oocyte water (nonyolk cytoplasmic water), which is two-to threefold slower in its diffusion rate than bulk water. In this regard, Ling et al (1967) reported a second smaller and more slowly exchanging water fraction in fully grown amphibian oocytes. Our data suggest that this slower exchanging water fraction may be within yolk platelets.…”
Section: Evidence For and Identification Of Two Water Compartments mentioning
confidence: 88%
“…Reduced diffusion of water in yolk is supported by other studies from this laboratory suggesting that the water in yolk platelets may not have time to migrate to a n ice crystal during quench freezing (Cameron et al,1 9 8 8~) . For comparison, isotopic measurements of water diffusion in fully grown amphibian oocytes have demonstrated a two-to threefold reduction in the diffusion coefficient of the water in reference to bulk water (Ling et al, 1967; see also Aguayo et al, 1986). This provides additional evidence that most, if not all, of the intraoocyte water is slowed in its diffusive properties in comparison with bulk water.…”
Section: Evidence For and Identification Of Two Water Compartments mentioning
confidence: 90%
“…Assuming that mannitol has access only to the adherent layer, the thickness of this layer was calculated from the surface area of the sac (Ling, Ochsenfeld & Karreman, 1967): a value of 89.5 +4.2 IX (SEM, n=8) was obtained. To determine the uptake of THO by the inner compartment it is therefore necessary to subtract from the measured uptake, that caused by the penetration of THO into the adherent layer.…”
Section: The Problem Of the Unstirred And Adherent Layersmentioning
confidence: 99%
“…A second procedure was to submit the bladder sac to a brief wash in a nonradioactive solution after loading with THO. According to Ling et al (1967) it takes no more than 0.02 sec for THOlabeled water to diffuse out from an adherent layer 10 g thick. In our case the thickness of the film seemed to be larger.…”
Section: The Problem Of the Unstirred And Adherent Layersmentioning
confidence: 99%